THE IMPACT OF VARIED BRAND SOCIAL CONTENT ON LOYALTY PROGRAM MEMBERS: AN EVALUATION - Ichwanudin, Wawan; Dwika Ayu Amrita, Nyoman; Aripin, Zaenal (Yayasan Kreatif Indonesia Emas, 2024)
This study evaluates the impact of diverse brands' social content on loyalty program members, with a focus on consumer perception, engagement and loyalty. Brand social content, including images, videos, reviews and promotions, is key to building strong relationships between brands and consumers in the ever-evolving digital era. Using a literature study research method, this research analyzes related literature to explore how variations in brand social content influence loyalty program members. The analysis results show that variations in brand social content have a significant impact on consumer perceptions of the brand. Varied content allows brands to reach and interact with loyalty program members in a variety of contexts and situations, broadening the relevance and depth of messages delivered, and creating stronger emotional connections. In addition, content variety can also increase loyalty program member engagement through active and participatory interactions on social media platforms. This can create a more valuable and satisfying experience for loyalty program members, as well as strengthen long-term relationships between brands and consumers. Furthermore, varied brand social content can also increase the level of consumer loyalty to the brand. By presenting content that is relevant, inspiring and engaging, a brand can strengthen emotional ties, expand the scope and relevance of the brand in consumers' daily lives, and enrich their experience with the brand. In order to achieve optimal marketing goals, brands must consider the diversity of content presented to loyalty program members to ensure maximum levels of engagement and loyalty.